PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA - Suryati, Yayat (Pusat Pengembangan Pendidikan dan Penelitian indonesia (P4I), 2025)
Most students perceive mathematics as a subject that is quite difficult to understand, resulting in a lack of interest in learning mathematics, which in turn affects their low academic performance in the subject. The low achievement in mathematics can be seen from the results of daily quizzes. The implementation of the cooperative learning model of the Make a Match type is very suitable for improving students’ understanding of mathematical concepts, as this model includes game-like elements that can positively impact students’ learning outcomes. The aim of this research is to determine whether the application of the cooperative learning model of the Make a Match type can improve the mathematics learning outcomes of Grade VII A students at SMP Negeri 2 Pandeglang. This research is a Classroom Action Research conducted in two cycles. The subjects of this study are the Grade VII A students of SMP Negeri 2 Pandeglang. The data sources were obtained through tests, observation sheets, and documentation, with data analysis comprising both quantitative and qualitative data. The research results showed that the average mathematics score of the students increased from a pre-cycle average of 60 with a mastery level of 26%, to an average of 72 in Cycle I with a mastery level of 68%, and an average of 81 in Cycle II with a mastery level of 86%. The N-Gain score improvement was 0.30 in Cycle I and 0.53 in Cycle II, which falls into the medium category. Therefore, the conclusion of this study is that the application of the Make a Match type cooperative learning model can improve the mathematics learning outcomes of Grade VII A students at SMP Negeri 2 Pandeglang. ABSTRAKSebagian besar siswa merasa pelajaran matematika adalah pelajaran yang cukup sulit dipahami, sehingga siswa kurang tertarik belajar matematika dan berimbas terhadap hasil belajar matematika siswa rendah. Data hasil belajar matematika siswa yang rendah dapat dilihat dari hasil ulangan harian. Penerapan model pembelajaran kooperatif tipe Make a match ini sangat cocok digunakan untuk meningkatkan pemahaman konsep matematika siswa, karena model pembelajaran ini ada unsur permainannya dan akan berimbas pada hasil belajarnya yang dapat meningkat. Tujuan penelitian ini untuk mengetahui penerapan model pembelajaran koperatif tipe make a match dapat meningkatkan hasil belajar matematika siswa kelas VII A SMP Negeri 2 Pandeglang. Penelitian ini Penelitian Tindakan Kelas dengan dua siklus. Subjek dalam penelitian ini adalah siswa kelas VII A SMP Negeri 2 Pandeglang. Sumber data hasil penelitian diperoleh dari hasil tes, lembar observasi dan dokumentasi dengan analisis data berupa data kuantitatif dan kualitataif. Dari hasil penelitian didapat nilai rata – rata hasil belajar matematika siswa dari pra siklus 60 dengan persentase ketuntasan 26 %, siklus I rata – rata 72 dengan tingkat ketuntasan 68% dan siklus II rata – rata 81 dengan tingkat ketuntasan 86%, sedangkan nilai peningkatan N-Gain pada siklus I sebesar 0,30 dan siklus II sebesar 0,53 dengan kategori sedang. Maka kesimpulan dari penelitian ini yaitu penerapan model pembelajaran koperatif tipe make a match dapat meningkatkan hasil belajar matematika siswa kelas VII A SMP Negeri 2 Pandeglang.